Graft and Corruption Practices Among Selected Public Officials in Mindanao, Southern Philippines - Amer Husain L. Laut; Abdul Azis G. Mariano; Fay Elaine B. Ontolan; Nimfa L Baracamonte; Christian T.N Aguano; Sulpecia L. Ponce (Jurnal Studi Pemerintahan, 2013)
This study aims to examine the graft and corruption practices among selected public officials in southern Philippines. The study is qualitative in nature making use of case study method in which an indepth analysis of primary data obtained from eight informants, four of whom are town mayors and their four incumbent municipal treasurers, is employed. The findings revealed that the mayor informants got elected through vote buying and bribery. Politics and family matters intersect as informants are supported by their families during election who used guns, gold and goons to ensure election victory. The clannish nature of the community finds expression also in the selection of relatives in municipal employment and in accessing municipal resources. The most prevalent corruption practice disclosed by the informants is amassing the internal revenue allotment (IRA) for personal purposes in order to recover the huge amount of money spent during election. Other types of corruption practices also include falsification of documents, nepotism, bribery, kickbacks, and evasion of public bidding. These public officials also do not seem to perform official duties in their towns as they live outside of their municipalities. Interagency involvement of corruption among different government agencies in the areas studied are also uncovered. Moreover, the perceived negative effects of corruption are manifested in the poor delivery of the community’s basic social services in health, water supply, education, and security protection. Corruption also adversely affects the construction of community infrastructure facilities and the establishment of an equitable and solid economic base. The study has implications to the strict policy implementation of the provisions of the 1991 Local Government Code of the Philippines, The AntiGraft and Corrupt Practices Act, and other pertinent laws in order to improve the transparency, integrity and accountability of public officials not only in southern Philippines but also in the entire country.